How women, designated as poor, reconstruct identities and ways of life? — the PRSI or the processes of re-qualifying social-identity - de Fátima Toscano, Maria (Journal of Education Culture and Society, 2020)
The sociological qualitative analysis of social identities and of the meanings of social action, the grounded theory and the ‘writing as analytical praxis qualitative-method’ have permitted me the co-creation of women biographies of un-qualifying/re-qualifying — oral discourses about their migration at the Pays Basque. I argue that the “poverty studies traditions” reproduce and contains seven (7) epistemological obstacles and formulations on negative terms, and I underline theoretical contributors to the Identities Sociology, discussing the oppositions “personal/social” (Social-Psi), and “determined-objectives identities/assumed-subjective identities” (Karl Marx, Émile Durkheim, Talcott Parsons and Pierre Bourdieu). So, I define “social identities” as the way the social-actor becomes a social-sujet (on the tradition of Touraine), considering three components (to explain). Defining oral discourses as the condition to co-construct the social experience, I identify and explain, at the re-qualifying processes: 1) several reaction phases – on positive terms – and social-identities territory’s implicated, as multiple meanings of the social action and identity-strategies (Risc, Strategic-Sacrifice); 2) four identity resources-capitals negotiated, affected, connected or stimulated.